Aromatization of n-C7–n-C9 alkanes on a Pt/KZSM-5(deAl) catalyst. Issue 4 (6th January 2023) - Zhou, Qiuming; Wang, Sen; Wu, Zhiwei; Qin, Zhangfeng; Dong, Mei; Wang, Jianguo; Fan, Weibin
Abstract : The prepared Pt/KZSM-5(deAl) catalyst through an AHFS and K2 CO3 post-treatment method exhibits superior performance for n -C7 – n -C9 alkane aromatization, with an aromatic selectivity and catalytic stability of >75% and >80 h, respectively. Abstract : Alkane aromatization is a significant supplementary route for the preparation of value-added aromatic products. Although ZSM-5 zeolites have been widely used in alkane aromatization, they always exhibit low catalytic stability, due to the diffusion limitation of medium-pore structures, resulting in rapid deactivation. Moreover, the excessive strong acid sites of ZSM-5 also induce a serious cracking reaction. To overcome these issues, the pore structure and acidic property of the ZSM-5 zeolite were controllably regulated using an ammonium hexafluorosilicate (AHFS) and potassium carbonate (K2 CO3 ) post-treatment method. After loading Pt, the Pt/KZSM-5(deAl) catalyst showed an aromatic selectivity as high as 75.4%, with an n -heptane conversion of 96.1%, at 550 °C and ambient pressure. More importantly, the catalytic lifetime reached 234 h. Even for the aromatization of n -octane and n -nonane with a larger molecular size, Pt/KZSM-5(deAl) still gave high aromatic selectivities of 82.7% and 83.4%, and n -octane and n -nonane conversions of 92.8% and 87.1%, along with a catalytic lifetime higher than 80 h. The results of XRD, N2 sorption, NH3 -TPD, Py-IR, TEM/STEM, H2 -TPR, CO-DRIFT and XPS indicated that using AHFS and K2 CO3 post-treatment can not only produce more mesopores to facilitate the diffusion of aromatic products, but also reduce the amount and strength of strong acid sites in ZSM-5 to avoid the over-cracking reaction. Moreover, the generated defect sites due to dealumination and the residual potassium ions (K + ) on the zeolite enhanced the interaction between Pt and ZSM-5 zeolite that effectively suppresses the aggregation and sintering of Pt particles.